Laser transillumination of interphalangeal joints of women suffering from rheumatoid diseases - Boerner, Ewa; Bauer, Joanna; Szewczyk, Anna; Podbielska, Halina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Experimental set-up consisted of He-Ne laser with optics for collimated illumination, special holder for placing the finger (perpendicular to optical axis, dorsal or ventral site towards camera), and CCD camera was constructed for performing the transillumination examination of proximal interphalangeal joints of 19 healthy female adult volunteers and 21 female patients suffering from joints inflammation. The transillumination images of ill and healthy subjects were compared by histogram analysis. The images were captured from dorsal and ventral side of the fingers. It was found that the mean grey level values in images taken at the dorsal side (laser beam travels from the ventral side) are lower than for the opposite direction. It was also concluded that healthy volunteers have joints more transparent to visible light, so the mean grey level values in captured images were higher. It was possible to observe the changes in images intensity of patients subjected to the anti-inflammation therapy, what may allow for monitoring the efficacy of the therapy.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 153-160
Keywords: optyka; laser transillumination; interphalangeal joints